THE RELATIONSHIP BETWEEN FAMILY SUPPORT WITH THE SUCCESS OF EXCLUSIVE BREAST FEEDING TO WORKING MOTHERS IN THE WORKING AREA OF PANOMBEIAN PANEI PUSKESMAS, SIMALUNGUN DISTRICT - Nur Mazdalifah (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2021)
One of the efforts to maintain children's health is aimed at preparing healthy, intelligent, and qualified next generations as well as reducing child mortality. Efforts to maintain child survival are carried out from the time the fetus is still in the womb, when it is born, after delivery, and until it is 14 (eighteen) years old. This indicator measures the management capacity of the Mother and Child Health (KIA) program in providing comprehensive neonatal services. Services provided during nconatal visits are examinations according to the Integrated Management of Young Infants (MTBM) standards and newborn care counseling including exclusive breastfeeding and umbilical cord care (Indonesian Health Profile, 2014). The purpose of this study was to determine the relationship between family support and the success of exclusive breastfeeding for working mothers in the work area of ​​the Panombeian Panei Health Center, Simalungun Regency, in 2017. This type of analytic study uses a cross-sectional approach. The population of this research is all working mothers who have babies aged 7-12 months in the working area of ​​the Panomberan Health Center as many as 45 people as of July 2017. The sample in this research is SCmus 1: working people who have babies aged 7-12 months in the working area of ​​the Puskesmas: There are 45 pots per July 2017. The sampling technique in this study uses total sampling.